16S rDNA sequencing analyzes differences in intestinal flora of human immunodeficiency virus (HIV) patients and association with immune activation. Issue 2 (1st February 2022) - Mingjun, Zhang; Fei, Mo; Zhousong, Xu; Wei, Xu; Jian, Xu; Yuanxue, Yi; Youfeng, Shen; Zhongping, Chen; Yiqin, Long; Xiaohong, Zhao; Ying, Cheng; Zhenbing, Wang; et al.
ABSTRACT: To clarify the influence of HIV on the intestinal flora and the interrelationship with CD4 T cells, the present study collected stool specimens from 33 HIV patients and 28 healthy subjects to compare the differences in the intestinal flora and CD4 T cells in a 16S rDNA-sequencing approach. ELISA was used to detect the expressions of interleukin 2 (IL-2), IL-8, and tumor necrosis factor-α (TNF-α). Meanwhile, correlation analysis with the different bacterial populations in each group was carried out. The results revealed that Alpha diversity indices of the intestinal flora of HIV patients were markedly lower than that of the healthy group (p < 0.05). The top five bacterial species in the HIV group were Bacteroides (23.453%), Prevotella (19.237%), Fusobacterium (12.408%), Lachnospira (3.811%), and Escherichia-Shigella (3.126%). Spearman correlation analysis results indicated that Fusobacterium_mortiferum, Fusobacterium, and Gammaproteobacteria were positively correlated with TNF-α (p < 0.05), whereas Ruminococcaceae, Bacteroidales was negatively correlated with TNF-α (p < 0.05). Additionally, Agathobacter was positively correlated with contents of IL-2 and IL-8 (p < 0.05), whereas Prevotellaceae, and Prevotella were negatively correlated with IL-8 content (p < 0.05). Furthermore, the top five strains in the CD4 high group (≥350/mm 3 ) included Bacteroides (23.286%), Prevotella (21.943%), Fusobacterium (10.479%), Lachnospira (4.465%), and un_f_Lachnospiraceae (2.786%). Taken together, the present study identified that Fusobacterium and Escherichia-Shigella were specific and highly abundant in the HIV group and a correlation between the different bacterial flora and the contents of IL-2, IL-8, and TNF-α was revealed.